Cognitive function and life quality of patients with moderate-to-severe obstructive sleep apnea-hypopnea syndrome in China. (4th March 2021) - Liu, YeHai; Han, JiangYin; Ning, Lin; Chen, LiJuan; Jiang, Xiao; Ke, AnRan; Zhang, YinHua
ABSTRACT: Objective : To investigate the correlation between cognitive function and quality of life in patients with moderate to severe OSAHS, and to further analyze the impact of cognitive domains on QoL in patients with OSAHS. Methods : Pearson analysis was applied to explore the correlation between MoCA score and SAQLI score. It was conducted by collecting the clinical characteristics of patients and the Epworth Sleepiness Scale and Sleep Quality Scale. T- test, a non-parametric test (Mann-Whitney) or chi-square test, and Pearson analysis were used to analyze the relationship between MoCA score and patient clinical characteristics, sleep variables, and SAQLI score. Results : The SAQLI score of the MCI group significantly decreased. Patients in the MCI group had a higher WHR, higher alcohol intake, and a history of hypertension were firmly related to the poor SAQLI (P < 0.05). The Epworth sleepiness scale (ESS) score increased in the MCI group, and the AHI and ODI elevated significantly, which was related to the poorer SAQLI as well (P < 0.05). Conclusion : Cognitive impairment in OSAHS patients is related to QoL reduction. Keywords : cognitive function; Montreal cognitive assessment; obstructive sleep apnea hypopnea syndrome; quality of life; sleep apnea quality of life index